Strategies for Integrating Animated Videos to Improve Students' Arabic Speaking Skills at Junior High School - Hadi Mar'ei Zain; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
Teaching Arabic speaking skills (maharah al-kalam) at the madrasah level remains challenging because instruction often emphasizes grammar and written exercises while providing limited opportunities for contextual oral practice. This qualitative descriptive study examined how animated videos were integrated into Arabic instruction at MTsN 1 Pekanbaru and how teachers perceived their contribution to students' engagement and speaking development. The study was conducted on May 2, 2026. Data were obtained through classroom observation and semi-structured interviews with Arabic language teachers, then organized into four analytical themes: classroom use of animated videos, teacher planning strategies, student engagement, and support for speaking practice. The findings indicate that teachers used short, curriculum-aligned animated dialogues within a sequence of vocabulary preparation, guided viewing, pausing and questioning, imitation, and follow-up speaking activities. Teachers considered animated videos useful for contextualizing vocabulary, modeling pronunciation and intonation, and reducing the monotony associated with textbook-centered instruction. The videos also appeared to encourage attention, oral responses, repetition, and willingness to participate. Their instructional value, however, depended on careful selection, manageable duration, clear audio, alignment with learning objectives, and the availability of basic equipment. Preparation time and limited access to suitable materials remained important constraints. The study concludes that animated videos are most productive when used as structured prompts for interaction rather than as passive entertainment. Because the evidence is qualitative and site-specific, the findings describe pedagogical practices and perceived benefits rather than establishing causal effectiveness.